11th AIAA Aviation Technology, Integration, and Operations (ATIO) Conference 2011
DOI: 10.2514/6.2011-6924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Uncertainty on Deterministic Runway Scheduling

Abstract: Active runway scheduling involves scheduling departures for takeoffs and arrivals for runway crossing subject to numerous constraints. This paper evaluates the effect of uncertainty on a deterministic runway scheduler. The evaluation is done against a firstcome-first-serve scheme. In particular, the sequence from a deterministic scheduler is frozen and the times adjusted to satisfy all separation criteria; this approach is tested against FCFS. The comparison is done for both system performance (throughput and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…The average delay of the delay-optimal simulation was not less than that of the first-come-first-served simulation. This is in contrast to stand-alone analysis of delay-optimal schedulers, [6][7][8][9][10][11][12] which showed that they reduce delays and increase throughput relative to simple algorithmic models of human controllers.…”
Section: Fcfs Grpcontrasting
confidence: 66%
See 2 more Smart Citations
“…The average delay of the delay-optimal simulation was not less than that of the first-come-first-served simulation. This is in contrast to stand-alone analysis of delay-optimal schedulers, [6][7][8][9][10][11][12] which showed that they reduce delays and increase throughput relative to simple algorithmic models of human controllers.…”
Section: Fcfs Grpcontrasting
confidence: 66%
“…The GRP simulation did not measurably increase the throughput rate of runway 17R or decrease average departure delay despite other research [6][7][8][9][10][11][12] that shows in standalone analysis that optimal departure scheduling can decrease delay. Future research could investigate other traffic scenarios, including runway crossings in the optimal scheduling process, and better prediction and control methods to see if optimal scheduling can increase the runway throughput.…”
Section: Future Workmentioning
confidence: 63%
See 1 more Smart Citation
“…Airport surface scheduling optimization has been an active field for research. Ioannis Simaiakis et al developed a queuing model of the departure process in order to describe quantitatively how queues form on the surface and what factors lead to the increased taxi-out times [1].Andrea D' Ariano et al studied the problem of sequencing aircraft take-off and landing operations at congested airports, but the real time of the solution was not good [2].Ying Dong et al proposed that the airport ground system can be regarded as an airport network topology and established an optimization model [3].Gautam Gupta et al evaluated the effect of uncertainty on a deterministic runway scheduler [4].Atkin et al used a model to predict the delays at the stands or the runway in order to absorb this time at the stand, but they did not analyze the delays at hotspot [5]. Christofas Stergianos et al investigated the importance of the pushback process in the routing and scheduling problem [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a trajectory-based air traffic management system, investigation of predictability on the surface is not just beneficial to the airport operations but could also improve performance in the downstream. However, in the context of airport surface operation management, performance assessment has mainly been conducted with respect to delay [1][2][3][4] , capacity [5][6][7][8] and efficiency 3,9,10 . Little work has been done to measure predictability, even though various stakeholders recognize the importance of predictability 11,12 .…”
Section: Introductionmentioning
confidence: 99%